A study on Antibiotic Resistance: An Analysis of Molecular Mechanisms and Therapeutic Implications - Kazi Kutubuddin; Heena Shaikh (International Journal of Antibiotics, 2026)
Antibiotic resistance (AR) represents one of the most critical existential threats to global public health, rapidly eroding the efficacy of established antimicrobial therapies and portending a return to the pre-antibiotic era. This analysis explores the intricate molecular landscape defining this crisis, focusing specifically on the primary mechanisms of action (MoA) utilized by major antibiotic classes—including cell wall inhibitors, protein synthesis inhibitors, and nucleic acid synthesis inhibitors—and the corresponding, diverse mechanisms of resistance (MoR) evolved by pathogenic bacteria. The core MoR identified involve: (1) Enzymatic Inactivation, notably achieved through the widespread proliferation of $beta$-lactamases; (2) Target Site Modification, structurally altering critical binding sites (e.g., PBP2a in MRSA); and (3) Reduced Intracellular Concentration, mediated by enhanced efflux pump activity or decreased membrane permeability. These MoR are often encoded on mobile genetic elements, facilitating rapid horizontal transfer across species. Understanding the precise interplay between MoA and MoR is paramount, as current drug discovery efforts struggle to keep pace with the velocity of bacterial adaptation. The imperative is clear: a radical paradigm shift toward non- traditional therapeutics and resistance-breaking strategies is urgently required to preserve the foundation of modern medicine.
Keywords: Enzymatic inactivation; Target site modification; antibiotic resistance; antibiotics; intercellular concentration